The praxis and politics of building urban dashboards. (December 2016) - Kitchin, Rob; Maalsen, Sophia; McArdle, Gavin
Abstract: This paper critically reflects on the building of the Dublin Dashboard – a website built by two of the authors that provides citizens, planners, policy makers and companies with an extensive set of data and interactive visualizations about Dublin City, including real-time information – from the perspective of critical data studies. The analysis draws upon participant observation, ethnography, and an archive of correspondence to unpack the building of the dashboard and the emergent politics of data and design. Our findings reveal four main observations. First, a dashboard is a complex socio-technical assemblage of actors and actants that work materially and discursively within a set of social and economic constraints, existing technologies and systems, and power geometries to assemble, produce and maintain the website. Second, the production and maintenance of a dashboard unfolds contextually, contingently and relationally through transduction. Third, the praxis and politics of creating a dashboard has wider recursive effects: just as building the dashboard was shaped by the wider institutional landscape, producing the system inflected that landscape. Fourth, the data, configuration, tools, and modes of presentation of a dashboard produce a particularised set of spatial knowledges about the city. We conclude that rather than frame dashboard development in purely technical terms, it is important to openly recognize their contested and negotiated politics and praxis.